Paciente femenino de 86 años con insuficiencia respiratoria aguda. - Pozo Argoti, Thalya Estefanía (2020)
In the present case study, acute respiratory failure is addressed in an 86-year-old female patient who came to the emergency area due to a clinical picture of 3 days of evolution characterized by a choking sensation, dry cough, thermal rise and pain in the hypogastrium. The objective of this study is to analyze the pathophysiological and clinical profile of patients with acute respiratory failure, thus laying the foundations to analyze the course of the disease and establish the strategies for its treatment. The follow-up carried out to the present case study, due to the existence of risk factors such as arterial hypertension and aggravating factors such as septic shock, this case had an unfavorable outcome despite the different pharmacological and ventilatory strategies used, that is why The author encourages the reader to take into consideration all the clinical and pathophysiological aspects addressed in this case to develop new strategies for the management of this pathology.